Kepatuhan Pajak Perusahaan Terbuka Modal Asing berdasarkan Laporan Keuangan Wajib Pajak - Mantiri, Jefry Rentje Durand; Wikarya, Uka (Direktorat Jenderal Perbendaharaan, Kementerian Keuangan, 2024)
Taxes are the largest source of state revenues to finance the public expenditures. However, since 2010 the tax revenue target has never been achieved. This is partly due to the low level of tax compliance. For this reason, it is necessary to audit the submitted SPT. This study analyzes the factors in the Financial Statements that can be indicators in determining audit priorities. The data used are SPT data and audit results for the 2015-2019 Fiscal Year, with a sample of 87 PMA companies listed on the IDX until 2015. This study uses panel data regression method with random effect model. The results of the study found that in determining the prioritized WP PMA in the audit, DGT needs to pay attention to indicators, namely: WP with large ROA and DER. In addition, WP PMA in the manufacturing sector can also be an indicator of priority audit.